Study of economic feasibility with the rainwater utilization in a metropolis of the Amazon, Brazil (Research, Society and Development, 2020)
The capture and storage of rainwater is an alternative for its supply, both in regions of the Brazilian semiarid and in other regions. This was evident between the years 2012 and 2017, as the longest drought in history, in which Brazil experienced a critical moment in relation to water availability in large urban centers, in terms of rainfall in the Southeast, especially in the metropolitan regions of the Rio de Janeiro, São Paulo and Belo Horizonte. In addition to this, there is the continued and historical scarcity in the Northeast states and the floods in the North and South of Brazil, and there is a generalized critical scenario, bringing up discussions about water risk management across the country. Therefore, this study evaluated the potential of using rainwater in the city of Belém-PA, with an emphasis on economic viability in the perception of residential consumers and the impact on the local drinking water concessionaire. Obtaining as results for the residential consumer in a first scenario the economic unfeasibility and for a second scenario the use of rain water is economically viable, besides this, for the supply concessionaire the use proves to be economically viable.